Gene‐specific facial dysmorphism in Axenfeld‐Rieger syndrome caused by FOXC1 and PITX2 variants. Issue 2 (24th November 2020) - Souzeau, Emmanuelle; Siggs, Owen M.; Pasutto, Francesca; Knight, Lachlan S. W.; Perez‐Jurado, Luis A.; McGregor, Lesley; Le Blanc, Shannon; Barnett, Christopher P.; Liebelt, Jan; Craig, Jamie E.
Abstract: Axenfeld‐Rieger syndrome is a genetic condition characterized by ocular and systemic features and is most commonly caused by variants in the FOXC1 or PITX2 genes. Facial dysmorphism is part of the syndrome but the differences between both genes have never been systematically assessed. Here, 11 facial traits commonly reported in Axenfeld‐Rieger syndrome were assessed by five clinical geneticists blinded to the molecular diagnosis. Individuals were drawn from the Australian and New Zealand Registry of Advanced Glaucoma in Australia or recruited through the Genetic and Ophthalmology Unit of l'Azienda Socio‐Sanitaria Territoriale Grande Ospedale Metropolitano Niguarda in Italy. Thirty‐four individuals from 18 families were included. FOXC1 variants were present in 64.7% of individuals and PITX2 variants in 35.3% of individuals. A thin upper lip (55.9%) and a prominent forehead (41.2%) were common facial features shared between both genes. Hypertelorism/telecanthus (81.8% vs 25.0%, p = 0.002) and low‐set ears (31.8% vs 0.0%, p = 0.036) were significantly more prevalent in individuals with FOXC1 variants compared with PITX2 variants. These findings may assist clinicians in reaching correct clinical and molecular diagnoses, and providing appropriate genetic counseling.